Showing and doing: Art & Science collaborations for Environmental sustainability - Stacy Levy (Nature-Based Solutions)
Art is becoming a new component in engineering and design collaborations to create nature- based solutions for site issues such as pollution control, stormwater runoff and habitat loss. In the last two decades there is a move to combine art with ecology to create a powerful tool for making change in ecological systems, particularly in urban nature. These works are inspired by nature and collaborate effectively with the natural process occurring on the site. Other outcomes of the projects are to increase ecological services on the site, and to involve and educate the human members of communities who live or work near the sites. The human users of the site can see and interact with the site issues while these very issues are being actively solved. Other species can reap the ecological benefits of expanded habitat and rainwater conservation. These projects have the added benefit of giving a visual explanation for the processes at work on the site. Artful Nature Based Solutions bring a new depth of understanding to the site issues because they regard the site through a combined focus of art and science. The essential aspect is the collaboration between artists and scientists. Having both the artist's and scientist's perspectives adds enrichment of ideas and vantage points to the solution. Science and engineering gains from the addition of a visual component as well as an expansion of the concept that art can bring to the issue. Though the projects do not always have quantitative data to back up their ecological effectiveness, the breadth of their communication and sense of making change in a troubled world are of great importance. The paper presents several exemplary cases of the collaboration realized through my work, which addressed stormwater runoff infiltration and water pollution, with implications for NBS.